Semiconducting Metal Oxides for Gas Sensing - Deng, Yonghui; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on the use of semiconducting metal oxides as gas sensing materials, including the sensing mechanism and sensing materials modification approach, while also providing a comprehensive introduction to semiconductor gas sensing devices. As an essential part of IoT (Internet of things), gas sensors have shown great significance and promising prospects. Therefore, studies on semiconducting metal oxides, one of the most important gas sensing materials, have increasingly attracted attention from various disciplines. The book offers a valuable reference guide to metal oxide gas sensing materials for undergraduate and graduate students alike. It will also benefit all researchers who investigate metal oxides nanomaterials synthesis and gas sensing with relevant frontier theories and concepts. Engineers working on research and development for semiconductor gas sensors will also find new ideas in sensor design. .
Preface -- Understanding of semiconducting metal oxides gas sensors -- Semiconducting metal oxides: morphology and sensing performance -- Semiconducting metal oxides: composition and sensing performance -- Semiconducting metal oxides: microstructure and sensing performance -- Gas sensing performance and evaluation criteria -- New approach to better performance -- Sensing mechanism of semiconducting metal oxides gas sensors -- Sensing devices of semiconducting metal oxides -- Concerns in practical gas sensor fabrications -- Applications of semiconducting metal oxides gas sensors -- Summary and outlook.
Keywords: Optical materials; Semiconductors; Materials; Materials -- Analysis; Surfaces (Technology).; Thin films; Microtechnology; Microelectromechanical systems; Optical Materials; Semiconductors; Materials Engineering; Characterization and Analytical Technique; Surfaces, Interfaces and Thin Film; Microsystems and MEMS